Induced Pluripotent Stem Cells (iPSC)-derived Mesenchymal Stem Cells (MSCs) Showed Comparable Effects in Repair of Acute Kidney Injury as Compared to Adult MSCs - Huang, Xiaowu; Wang, Huanhuan; Xu, Yong (Urology Journal, 2020)
Purpose: The study aimed to compare the therapeutic effects of iPSC-derived MSCs (iPSC-MSCs) and adult MSCs for acute kidney injury (AKI) therapy. Materials and Methods: Model rats with ischemia/reperfusion (I/R)-induced AKI were randomly divided into three groups (n=15 for each group) to receive transplantation of iPSC-MSCs, adult MSCs, or the saline control. After transplantation, engraftment and differentiation of both iPSC-MSCs and adult MSCs were detected in the transplanted sites. Serum creatinine and blood urea nitrogen (BUN) for renal function evaluation were measured, and histological assays were performed as well. Results: Compared with the saline control, both iPSC-MSCs and adult MSCs significantly (p<0.05 or 0.01) improved the renal function. Furthermore, iPSC-MSCs showed comparable effects in ameliorating tissue damage, reducing cell apoptosis and promoting vascularization with adult MSCs. Conclusion: This study compared the therapeutic effects of iPSC-MSCs and adult MSCs for AKI treatment. Both iPSC-MSCs and adult MSCs were observed with comparable effects in repair of AKI. The results indicated that iPSC-MSCs may serve as an alternative source of MSCs for stem cell-based therapy for AKI therapy.